2000
DOI: 10.1095/biolreprod62.5.1184
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Formation and Dynamics of γ-Tubulin and Nuclear Mitotic Apparatus Protein Distribution During Meiosis in Pig and Mouse Oocytes1

Abstract: This work focuses on the assembly and transformation of the spindle during the progression through the meiotic cell cycle. For this purpose, immunofluorescent confocal microscopy was used in comparative studies to determine the spatial distribution of alpha- and gamma-tubulin and nuclear mitotic apparatus protein (NuMA) from late G2 to the end of M phase in both meiosis and mitosis. In pig endothelial cells, consistent with previous reports, gamma-tubulin was localized at the centrosomes in both interphase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 36 publications
9
85
1
2
Order By: Relevance
“…In mouse oocytes, LGN-N-GFP localized to the spindle apparatus, but was not restricted to the spindle poles. This localization pattern is similar to that of NuMA, which is localized along the meiotic spindle microtubules in mouse oocytes [26]. We speculate that the localization difference between LGN (and LGN-N) on mitotic spindles in MDCK cells and LGN (and LGN-N) on meiotic spindles in mouse oocytes may stem from the different localization of NuMA.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In mouse oocytes, LGN-N-GFP localized to the spindle apparatus, but was not restricted to the spindle poles. This localization pattern is similar to that of NuMA, which is localized along the meiotic spindle microtubules in mouse oocytes [26]. We speculate that the localization difference between LGN (and LGN-N) on mitotic spindles in MDCK cells and LGN (and LGN-N) on meiotic spindles in mouse oocytes may stem from the different localization of NuMA.…”
Section: Discussionsupporting
confidence: 66%
“…Previously, researchers have reported that LGN regulates mitotic spindle organization in somatic cells by interacting with and inhibiting the microtubule binding and stabilizing activity of NuMA [16,18]. In mouse oocytes, instead of concentrating at the spindle poles like γ-tubulin, NuMA is localized along spindle microtubules [26], similar to the spindle localization of LGN. Therefore, excessive LGN might inhibit NuMA and consequently disturb the targeting of Kif2a and/or other microtubule depolymerizing factors to the spindle poles and ultimately result in elongated meiotic spindles in mouse oocytes.…”
Section: Discussionmentioning
confidence: 79%
“…The NuMA foci were translocated from the condensed chromosomes and became aligned at both poles of the meiotic spindle during the metaphase I and II stages. Comparing with previous studies, we found that NuMA distribution in rabbit species is similar to pig (Lee et al 2000) but different from mouse (Lee et al 2000, Tang et al 2004. In mouse oocytes, NuMA was localized along spindle microtubules (Lee et al 2000) and at cytasters (Tang et al 2004).…”
Section: Discussionsupporting
confidence: 58%
“…As the role in meiosis, NuMA appeared to localize to spindle poles of the meiotic pig and mouse oocytes and treatment with nocodazole disrupted the localization of NuMA (Lee et al 2000). In maturating Xenopus oocytes, the microinjection of NuMA antibodies perturbed the organization of the transient MT array and the meiotic spindle (Becker et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation